Serum Myelin Oligodendrocyte Glycoprotein and Myelin Protein Zero as Diagnostic Biomarkers in Diabetic Neuropathy - Murad, Abbas Mahmood; Majeed, Maysaa Jalal; Al-Ameri, Rafid Badri; AL-Haidari, Ahmed Salim (AL-Kindy College Medical Journal, 2023)
Background: Diabetic neuropathy can affect any peripheral nerve, including sensory neurons, motor neurons, and the autonomic nervous system. Therefore, diabetic neuropathy has the potential to affect essentially any organ and can affect parts of the nervous system like the optic nerve, spinal cord, and brain. In addition, chronic hyperglycemia affects Schwann cells, and more severe patterns of diabetic neuropathy in humans involve demyelization. Schwann cell destruction might cause a number of changes in the axon. study aims to evaluate serum myelin protein level as a predicting marker in the diagnosis of diabetic neuropathy and to prevent early neuropathy complications of type 2 diabetes.Subjects and methods: To achieve the purpose of the objective, this study involved 120 individuals divided into three groups. The first group included 40 healthy individuals; the second group included 40 type 2 diabetic patients with a diabetes duration of more than 5 years; and the last group included 40 type 2 diabetic patients with a diabetes duration of less than or equal to 5 years. The enzyme-linked immunesorbent assay (ELISA) system is used to detect serum MOG and MPZ.Results: both groups of type 2 diabetes patients had significant (p≤ 0.05) increases in serum myelin protein zero P0 (MPZ) and myelin oligodendrocyte glycoprotein (MOG).Conclusion: According to the results, myelin protein can be used to diagnose patients with diabetic neuropathy at an early stage. But it did not rise to the level of a biomarker due to a lack of sensitivity